Gaseous discs at intermediate redshifts from kinematic data modelling. Issue Volume 11:Issue S308(2015) (12th October 2016) - Kipper, R.; Tamm, A.; Tenjes, P.; Tempel, E.
Abstract: Our purpose is to measure thickness of gaseous discs in 0 < z < 1.2 galaxies. As gas dispersions are sensitive to scale height of gaseous discs, we model the kinematics of galaxies using Jeans equations. The resulting thicknesses of gaseous discs at higher redshifts are more thicker (and arbitrary) while nearby ones are thinner. We also found that clumpiness of galaxy is a possible indicator of the gas disc thickness.